2002
DOI: 10.1038/sj.bjc.6600623
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of human kallikrein gene 14 expression in breast tumours indicates association with poor prognosis

Abstract: KLK14 (formerly known as KLK-L6) is a recently identified member of the human kallikrein gene family. This family harbours several genes aberrantly expressed in various cancers as well as established (PSA/hK3, hK2) and potential (hK6, hK10) cancer markers. Similar to other kallikrein genes, KLK14 was found to be regulated by steroid hormones, particularly androgens and progestins, in breast and ovarian cancer cell lines. Preliminary studies indicated that KLK14 is differentially expressed in breast, ovarian, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 49 publications
3
23
1
5
Order By: Relevance
“…These data are in conflict to a recent RT-PCR study, which showed loss of KLK14 expression in 21 of 25 (84%) human breast cancer analysed ). However, our data are in agreement with another quantitative RT-PCR study that described much more abundant KLK14 expression (in 55 of 178 breast tumours) and a clear correlation of KLK14 expression and poor prognosis (Yousef et al, 2002a). The possible explanation for these disparities could be that our study and that of Yousef et al (2002a) used the more accurate quantitative RT-PCR technique.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These data are in conflict to a recent RT-PCR study, which showed loss of KLK14 expression in 21 of 25 (84%) human breast cancer analysed ). However, our data are in agreement with another quantitative RT-PCR study that described much more abundant KLK14 expression (in 55 of 178 breast tumours) and a clear correlation of KLK14 expression and poor prognosis (Yousef et al, 2002a). The possible explanation for these disparities could be that our study and that of Yousef et al (2002a) used the more accurate quantitative RT-PCR technique.…”
Section: Discussionsupporting
confidence: 92%
“…However, our data are in agreement with another quantitative RT-PCR study that described much more abundant KLK14 expression (in 55 of 178 breast tumours) and a clear correlation of KLK14 expression and poor prognosis (Yousef et al, 2002a). The possible explanation for these disparities could be that our study and that of Yousef et al (2002a) used the more accurate quantitative RT-PCR technique. The present study is the first to analyse KLK14 protein expression in a large cohort of human breast cancer specimens in comparison to matching normal breast tissues using a recently characterised KLK14-specific antibody (Felber et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations